Weaponization of Interdependence: Economic Dependency as a Tool of Global Power - Sumartono Sumartono; Nurul Fadhilah (Synergisia, 2026)
This article examines the concept of weaponization of interdependence, a strategy whereby state actors exploit global economic interdependence networks as instruments of geopolitical pressure and power. The study analyzes how actors such as the United States, China, and Russia leverage dominance over financial networks, technology supply chains, and energy infrastructure to achieve their foreign policy objectives. Through a qualitative approach employing systematic analysis of recent scholarly literature, the study finds that economic interdependence is no longer neutral but has transformed into a strategic tool in great power competition. These findings carry significant implications for global governance architecture and the economic resilience of developing states